2021
DOI: 10.1016/j.toxrep.2021.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of a glyphosate-based herbicide on the gut microbiome of three earthworm species (Alma millsoni, Eudrilus eugeniae and Libyodrilus violaceus): A pilot study

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Studies have been conducted on representatives of various taxonomic groups. Direct or indirect effects of administration of pesticide formulations on the gut microbiome were mainly detected in rats and mice, but there are data on the effects of pesticides on the gut microbiome of worms [ 175 ], pigs [ 176 ], fish [ 177 ], and honey bees. For example, glyphosate affects susceptibility of the gut microbiome of honey bees to pathogens, making them more vulnerable to infections [ 178 ].…”
Section: Health Effects After Pesticide Exposurementioning
confidence: 99%
“…Studies have been conducted on representatives of various taxonomic groups. Direct or indirect effects of administration of pesticide formulations on the gut microbiome were mainly detected in rats and mice, but there are data on the effects of pesticides on the gut microbiome of worms [ 175 ], pigs [ 176 ], fish [ 177 ], and honey bees. For example, glyphosate affects susceptibility of the gut microbiome of honey bees to pathogens, making them more vulnerable to infections [ 178 ].…”
Section: Health Effects After Pesticide Exposurementioning
confidence: 99%
“…Moreover, it has been shown that the ubiquitous presence of this herbicide in different ecosystems, such as rivers, induces a significant decrease in bacterial richness and diversity [44]. A significant impact on bacterial species loss by glyphosate has even been found in the earthworm microbiome [45].…”
Section: Bacteria Are Facing Extinctionmentioning
confidence: 99%
“…For example, more and more studies show that in some particular cases, (e.g. glyphosate and glyphosate-based herbicides) commercial formulations that contain an active compound along with other considered inert ingredients can be more toxic compared with the active compound alone that is used for classification [ [25] , [26] , [27] ]. In addition, hazards not properly described under CLP are constantly being identified, as for example cardiotoxicity, with considerable latency in manifesting adverse effects that bear a long-lasting risk to public health [ [28] , [29] , [30] ].…”
Section: Revision Of Clp Regulationmentioning
confidence: 99%